Genital mycotic infections with canagliflozin, a sodium glucose co-transporter 2 inhibitor, in patients with type 2 diabetes mellitus: a pooled analysis of clinical studies. (June 2014) - Nyirjesy, Paul; Sobel, Jack D.; Fung, Albert; Mayer, Cristiana; Capuano, George; Ways, Kirk; Usiskin, Keith
Abstract Objective: To characterize genital mycotic infections with canagliflozin, a sodium glucose co-transporter 2 inhibitor, in patients with type 2 diabetes mellitus (T2DM) using pooled data from Phase 3 studies. Research design and methods: Genital mycotic infections with canagliflozin 100 and 300 mg were evaluated in Population 1 (N = 2313; mean exposure [weeks]: canagliflozin, 24.3; placebo, 23.8), including patients from four placebo-controlled studies, and Population 2 (N = 9439; mean exposure [weeks]: canagliflozin, 68.1; control, 64.4), including patients from eight placebo/active-controlled studies (including older patients and those with renal impairment or high cardiovascular disease risk). Clinical trial registration: ClinicalTrials.gov, NCT01081834; NCT01106625; NCT01106677; NCT01106690; NCT01032629; NCT01064414; NCT01106651; NCT00968812. Main outcome measures: Adverse events suggestive of genital mycotic infections were recorded, with additional information collected using supplemental electronic case report forms. Results: In Population 1, genital mycotic infection incidence was higher with canagliflozin 100 and 300 mg than placebo (95% confidence intervals excluded zero) in females (10.4%, 11.4%, 3.2%) and males (4.2%, 3.7%, 0.6%). These were generally mild to moderate in intensity, none were serious, and few led to discontinuation. Most events with canagliflozin were treated with antifungal therapies, and median symptom duration following treatment initiation was similar across groups; few patients had >1 event (females, 2.3%; males, 0.9%). Findings with canagliflozin 100 and 300 mg versus control were similar in Population 2 (females: 14.7%, 13.9%, 3.1%; males: 7.3%, 9.3%, 1.6%); a low proportion of males underwent circumcision across groups. Most events with canagliflozin occurred within the first 4 months in females and first year in males; no consistent evidence of dose dependence was observed. Key limitations included lack of laboratory confirmation for most events and variable treatment methods. Conclusions: Genital mycotic infection incidences were higher with canagliflozin than control in patients with T2DM; events were generally mild to moderate in intensity and responded to standard treatments.